Anxiety and Depression Correlates at Age 10 in Children Born Extremely Preterm. (4th January 2021) - Moore, Phoebe S; Mokrova, Irina; Frazier, Jean A; Joseph, Robert M; Santos, Hudson P; Dvir, Yael; Hooper, Stephen R; O'Shea, T Michael; Douglass, Laurie M; Kuban, Karl C K
Abstract: Objective Anxiety and depression rates are known to be elevated in prematurely-born children and adolescents. This prospective study examines demographic, academic, and physical health correlates of anxiety and depression symptoms in a sample of 10-year-old children who were born extremely preterm. Methods Participants were 889 (51.2% male; 62.3% White) children who were born <28 weeks gestation. Child and family demographic data were collected at birth. When the children were 10, parents ( n = 871) and teachers ( n = 640) rated the level of anxiety and depression in children through the Child Symptom Inventory-4. Child academic functioning was assessed via the Wechsler Individual Achievement Test-III. Parents completed questionnaires about child academic functioning and physical health issues. Data analyses were conducted with multivariate linear modeling. Results Level of prematurity was significantly related to both parent and teacher reports of anxiety. Public health insurance and individualized education program (IEP) status were associated with both parent and teacher reports of depression. Hispanic ethnicity, public insurance, IEP status, and asthma were significantly associated with both parent-reported anxiety and depression. Gross motor impairment was associated with parent-reported anxiety and teacher-reported depression. Child obesity was associated with teacher reports of anxiety, while male sex was significantly related to teacher reports of depression. Conclusion This pattern of findings may suggest hypotheses for future research on models of the development and persistence of anxiety and depression within this particularly vulnerable group of children.